Step-by-step explanation
A geometric sequence is defined as:
![\begin{gathered} a_1=a*r^0=a*r^(1-1), \\ a_2=a*r^1=a*r^(2-1), \\ a_3=a*r^2=a*r^(3-1), \\ ... \\ a_7=a*r^6=a*r^(7-1), \\ ... \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/l1y22akbfzvoxriwzvi8ji5j08kx9hcg4r.png)
Where r ≠ 0 is the common ratio and a ≠ 0 is the first term of the sequence.
From the statement, we know that r = 2/3 and the first term is a = 5.
Replacing these numbers in the expression of the 7th term, we get:
Answer320/729